Lumbar spondylodiscitis mimicking cholecystitis: a case report and review of literature - Mirbagheri, Andia; Etminan, Nima; Schölch, Sebastian; Maier, Christopher; Perrin, Jason Michael; Enders, Frederik (Journal of neurological surgery. Part A, Central European neurosurgery, 2023)
Background: Lower back pain is a frequent cause of emergency department visits and one of the leading causes of the disease burden worldwide. The purpose of this case report and literature review was to discuss atypical abdominal entities mimicking spinal diseases typically presenting with lower back pain. Methods: A 79-year-old man presented with lower back pain and urinary incontinence after receiving a non-image-guided lumbar infiltration treatment 4 weeks prior to admission. The magnetic resonance imaging (MRI) highlighted multisegmental hyperintensities in the intervertebral disk spaces of the lumbar spine indicative for spondylodiscitis. Antibiotic treatment over a week did not lead to significant clinical improvement. Blood cultures, cardiologic, otorhinolaryngologic, and dental examinations turned out negative for a focus of infection. A computed tomography (CT) guided biopsy was indicated after discontinuation of antibiotic treatment for less than 24 hours. Rapid clinical deterioration with concomitant onset of abdominal pain resulted in the diagnosis of cholecystitis, which required cholecystectomy. We performed a systematic literature review using the Pubmed database for the keywords “spondylodiscitis,” “spine,” “abdominal,” and “cholecystitis,” to identify abdominal diseases that mimic spine pathologies and spinal diseases that mimic abdominal pathologies. Results: No other report in English literature of cholecystitis associated with initial onset of lower back pain was identified. Eighteen reports referred to abdominal conditions that mimic spinal diseases, among them a patient with cyclic lumbar back pain who received a lumbar spinal fusion who, after persisting symptoms led to further diagnostic procedures, was ultimately diagnosed with endometriosis. Spinal symptoms included paraplegia and urinary incontinence as results of acute aortic pathologies. Eleven reports presented spinal pain mimicking abdominal conditions including abdominal pain and diarrhea as well as have had surgical procedures such as an appendectomy before the spinal condition was discovered. Conclusion: Clinical symptoms of the spine such as lower back pain can be unspecific and lead to false conclusions in the presence of concomitant pathologies in MRI. Only clinical deterioration in our case patient prompted correction of the diagnosis on day 7. Initial workup for alternative common infectious foci such as lung and urinary tract was performed, but further abdominal workup despite the absence of abdominal symptoms may have led to an earlier diagnosis. Our literature review found several cases of misdiagnosed spinal and abdominal conditions. Some had undergone unnecessary surgical procedures before the right diagnosis was made. Because of the high incidence of symptoms such as lumbar back pain and abdominal pain, considering optimal patient care as well as economic aspects, it would be essential to conduct an interdisciplinary clinical management to avoid errors in the early stage of diagnostics.